How digital technology is reshaping the art of management - Maria Cesira Urzì Brancati; Maurizio Curtarelli; Sara Riso; Sara Baiocco (European Commission, Joint Research Centre (JRC), 2022)
This study describes how the digitisation of the workplace may contribute to the emergence of data-driven management, and how this, in turn, may affect work organisation and aspects of job quality, such as occupational health and safety. It summarises and defines the technologies that enable data-driven management and provides a snapshot of their diffusion across Europe. The paper shows how some technologies are fairly widespread, while other are found only in a minority of establishments. The descriptive analysis presented in this research report shows that the use of technologies enabling data-driven management may have both positive and negative impacts on workers and working conditions. Better establishment performance, provision of training, greater job complexity and worker autonomy are among the positive impacts associated with the presence of some digital technologies for data-driven management. By contrast, lower workers' well-being and a higher prevalence of reported psychosocial risks in the workplace are among the negative impacts at the establishment level. The paper suggests a number of measures to mitigate the potentially negative impact of data-driven management on workers' wellbeing.
Keywords: 330; data-driven management; algorithmic management; psychosocial risks; digitisation; work organisation; working conditions